Epidermal growth factor receptor and anaplastic lymphoma kinase mutation in adenocarcinoma lung: Their incidence and correlation with histologic patterns - Pankaj Gupta; Swarnalata Gowrishankar; Meenakshi Swain (Wolters Kluwer Medknow Publications, 2019)
Introduction: Epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) mutational analysis in adenocarcinoma lung are growing in importance as these tests are essential in guiding the use of targeted therapy. However, the prevalence of these mutations in various populations in India has not been studied. Furthermore, the correlation of histologic pattern with the mutation is not clear. Materials and Methods: A total of 64 biopsy-proven lung adenocarcinomas were selected. In 51 of these, EGFR mutational analysis was performed using Qiagen EGFR pyrosequencing kit and in 56 cases of these ALK1 immunohistochemistry (IHC) was done using ALK (D5F3) antibody and the Ventana Benchmark® XT automated IHC slide staining system for the detection of overexpression. The adenocarcinomas were classified into well, moderate, and poorly differentiated, and the histological pattern was recorded according to the WHO 2014 classification. Results: EGFR mutation was positive in 23 cases (45.10%) and positive ALK1 expression by IHC in 12 cases (21.43%). Both mutations were positive in two cases. Both mutations were seen in well-differentiated and moderately differentiated adenocarcinoma, and the expression was highest in tumors with a predominant acinar pattern. Conclusions: The incidence of both EGFR and ALK1 mutations is higher in the population studied and seem to correlate with a well differentiated, acinar pattern on morphology.